Donor site outcome after oral mucosa harvest for urethroplasty: a prospective study - Muppirala, Lakshmi Ramesh; Yekolla, Yuvaraju; Pogula, Vedamurthy Reddy; Gaddam, Yaswanth Kumar; Bathalapalli, Ravi Theja; Jagirda, Sayyed Faisal (International Journal of Research in Medical Sciences, 2025)
Background: Congenital or acquired defects of the male urethra may be repaired utilizing varied substitute materials, such as genital or extragenital skin and oral mucosa (OM). Currently, the application of OM has emerged as the most dependable and favoured alternative to urethral reconstructive surgery. This study aimed to examine oral morbidity and patient satisfaction within a uniform cohort of patients who underwent oral mucosa harvesting with a standardised procedure. Methods: The study was carried out in the Department of urology, Narayana medical college and hospital, Nellore between January 2023 to March 2025. 38 cases were included in the study, at the time of admission, detailed history, clinical examination and necessary radiological examination were done. Results: The results showed that 2 (5%) of 38 patients had early oozing. 3 cases (7%) had accidental lip and cheek bites in whom harvest site was not closed. The graft site was sutured in 26 patients (68.42%). In 8 patients (21.05%) the graft site was left open. At one month only 1 patient (2.63%) was unable to whistle and he was able to do so by 3 months. 2 patients (5.26%) had parotid swelling during first week of surgery which subsided at 2 weeks with conservative treatment. 24 patients (63.15%) of 38 had restricted mouth opening only during first week. Conclusions: Restricted mouth opening and Pain are the only long-term complications in our study which were not bother-some. Pain appears to be worse after suturing donor site. Bilateral buccal mucosal graft harvesting has no extra problems as compared to unilateral harvesting. Hence in case of long urethral stricture, two independent Strips are preferable than single strip involving lip.